Risk mitigating versus risk shifting: Evidence from banks security trading in crises - José-Luis Peydró; Andrea Polo; Enrico Sette; Victoria Vanasco (SSRN, 2023)
We show that risk-mitigating incentives dominate risk-shifting incentives in fragile banks. We study security trading by banks, as banks can easily and quickly change their risk exposure within their security portfolio. For identification, we exploit different crisis shocks and supervisory ISIN-bank-month-level data. Less capitalized banks take relatively less risk after financial stress shocks. Results hold within identical regulatory capital risk weights categories. Moreover, additional tests suggest that banks' own incentives, rather than supervision, are the main drivers. Results hold for the different crisis shocks since 2007/08, including the COVID-19 one. A model of bank behavior rationalizes our findings.
Keywords: G00; G01; G21; G28; G30; 330; risk shifting; financial crises; securities; bank capital; reach for yield; uncertainty; risk weights; supervision; franchise value; COVID-19